Relationship between Cognitive Function, Depression/Anxiety and Functional Parameters in Patients Admitted for Congestive Heart Failure - Feola, Mauro (Bentham Open, 2013)

(untitled)
Cognitive impairment, anxiety and depression have been described in patients with congestive heart failure (CHF). We analyzed in-hospital CHF patients before discharge with neuropsychological tests attempting to correlate with prognostic parameters. METHODS: All subjects underwent a mini mental state examination (MMSE), geriatric depression scale (GDS), anxiety and depression scale test (HADS). We evaluated NYHA class, brain natriuretic peptide (BNP), left ventricular ejection fraction (LVEF) and non-invasive cardiac output (CO). RESULTS: Three-hundred and three CHF patients (age 71.6 ys) were analysed. The mean NYHA class was 2.9±0.8, LVEF was 43.4±15.8%; BNP plasma level and CO were calculated as 579.8±688.4 pg/ml and 3.9±1.1 l/min, respectively. In 9.6% a pathological MMSE score emerged; a depression of mood in 18.2% and anxiety in 23.4% of patients were observed. A significant correlation between MMSE and age (r=0.11 p=0.001), BNP (r=0.64 p=0.03) but not between MMSE and NYHA class and LVEF was observed. GDS and HADS were inversely correlated with NYHA class (r=0.38 p=0.04) and six-minute walking test (r=0.18 p=0.01) without an association with objective parameters in CHF (BNP, LVEF and cardiac output). At multivariate analysis only MMSE and BNP are inversely correlated significantly (p=0.019 OR=-0.64, CI=-042-0.86). CONCLUSIONS: in-hospital CHF patients may manifest a reduction of MMSE and important anxiety/depression disorders. The results of the study suggest that the presence of cognitive impairment in older CHF patients with higher BNP plasma level should be considered. In admitted CHF patients anxiety and depression of mood are commonly reported and influenced the perception of the severity of illness.